The Application of Innovative Technology on Internal Border Control in Schengen Area - Septyanto Galan Prakoso; Eryan Dwiki Effendi; Rizaldi Yazid Purnama Putra; Rameez Ali Surya Negara; Niki Wahyu Sayekti (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2021)
This article or writing aims to discuss the application of technology and certain mechanism as the impact of a disruptive era on internal border control in the Schengen area. The problem is focused on the internal border system which got reintroduced as a countermeasure against the 2015 Migrant Crisis in Europe. The analysis conducted in this research will measure whether the application of technology gives a practical benefit in alleviating internal border controls or negative impact such as discrimination towards refugees and immigrants in the Schengen area. In order to approach this problem a theoretical reference is used from international relations’ perspective, as a part of the political science greater scope on the issue. The data is collected through library research and analyzed qualitatively. This study concludes that various improvements and improvisation were made in the implementation of border controls. There are several steps taken by the EU for border control checks by utilizing technology such as Visa Information System (VIS), Schengen Information System (SIS), European Travel Information and Authorization System (ETIAS), and FRONTEX. These technologies allow Schengen states to share visa data about individual who enters European Union from its various borders, enable seamless cooperation regarding border controls and law enforcement and visitor tracking between countries. This study conclude that the application of innovative technology on internal border control in Schengen Area is well applied and projectively very useful to tackle the security concerns and conflicting interests within the Schengen area and remove the needs of unnecessarily long physical internal border controls.